Plan de mejora en el Sistema de Prevención de Riesgos Laborales, a partir del análisis del proceso de producción de Queso Semiduro de la Unidad Empresarial de Base Combinado Lácteo Pinar del Río. - Flores Pila, Iván Rodrigo (2011)
The Unidad Empresarial de Base Combinado Lácteo Pinar del Río is dedicated to the production, distribution and sale of such milky products as, milk, different types of cheese, yogurt and ice cream. For the realization of the work one we take in account the following general objective: To propose a plan of improvement in the system of prevention of risks of labor accidents, for the process of production of cheese semi-hard of the Unidad Empresarial de Base Combinado Lácteo Pinar del Río in order to give execution to the same one the following specific objectives was traced: To carry out the bibliographical studies about Industrial Security and Systems of Prevention of Labor Risks in productive processes. To discover the actual conditions of industrial security in the area of processes of production of cheeses semi-hard. To propose solutions to the factors of labor risks detected in the area of production of cheeses semi-hard.